2014
DOI: 10.4103/2141-9248.126627
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxycut-induced liver toxicity

Abstract: In the recent era, use of various nutritional supplements is highly encouraged amongst the people of United States. Weight loss supplements are major part of the nutritional supplements and their usage is unregulated in the US. Obesity is a major health concern in the US and Americans spend around $30 billion a year for weight loss supplements. At times, these supplements can be responsible for documented or undocumented adverse drug effects. The health consequences related to these supplements are often overl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…A further case, reported by Sharma et al (2010), involved a 19-year-old man who took the product for fat burning and muscle building. More recently, Kaswala et al (2014) reported the case of a 27-year-old man who was studying to be a physical trainer and had been taking Hydroxycut ® along with other supplements (black powder, mitotropin, xenadrine, etc.). Finally, Haimowitz et al (2015) described a fulminant liver failure in a 23-year-old man after consumption of Hydroxycut ® for 2 months.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A further case, reported by Sharma et al (2010), involved a 19-year-old man who took the product for fat burning and muscle building. More recently, Kaswala et al (2014) reported the case of a 27-year-old man who was studying to be a physical trainer and had been taking Hydroxycut ® along with other supplements (black powder, mitotropin, xenadrine, etc.). Finally, Haimowitz et al (2015) described a fulminant liver failure in a 23-year-old man after consumption of Hydroxycut ® for 2 months.…”
Section: Discussionmentioning
confidence: 97%
“…The search started from November 2008 (because we desired to update our previous work on green tea hepatotoxicity, Mazzanti et al 2009) and extended to March 2015, without any language restriction. Cases of hepatotoxicity induced by Hydroxycut ® published in this period (Fong et al 2010;Sharma et al 2010;Kaswala et al 2014;Haimowitz et al 2015) were not included in this review, owing to the withdrawal of the product from the market in July 2009; nevertheless, they have been mentioned in the Discussion section.…”
Section: Methodsmentioning
confidence: 97%
“…G. cambogia was also a main active ingredient in the weight-loss supplement Hydroxycut ® (Iovate Health Sciences, Inc., Oakville, ON), which has known hepatoxicity[11-16]. In May 2009, the FDA issued a consumer warning recalling all Hydroxycut ® products due to 23 hepatotoxicity cases.…”
Section: Discussionmentioning
confidence: 99%
“…83 Hydroxycut was again reformulated without these substances, but the older formulations still appear to be available. 88,89 Some cases of AEs continue to appear even with the newer formulation. 90,91…”
Section: Researchmentioning
confidence: 99%